c - 9 (b, 2016)
Novel based on the death of Swami Vivekananda, 1863-1902.
Novel.
In Bengali; includes passages in English.
Keywords: Vivekananda, -- Swami, -- 1863-1902 -- Death -- Fiction; Vivekananda, -- Swami, -- 1863-1902.